Contemporary business - Kurtz, David L. (South-Western Cengage Learning, 2009)
These audio reviews contain key chpter concepts and learning objectives allowing you to review classroom material anywhere, any time. Listen to them while you're exercising, inyour car, or even while walking through capus on your way to class. Step to the head of the class, because you'll be prepared in a completely new way.